The treatment of criminal offenders: a history - Burkhead, Michael Dow (McFarland, 2007)
The principal issues -- Treatment and punishment : a brief history of the American prison -- The history of biologically based treatment -- The history of psychologically based treatment -- The state of the science : cognitive-behavioral intervention -- The principles of effective intervention -- The treatment of special populations -- Faith-based programs -- The science of sin : correctional treatment today